설문지 분석법에 의한 肝·心·脾·肺·腎病의 標準 症狀 및 男女差異 硏究 - 권혁(Hyuck Kwon); 이인선(In Seon Lee); 김규곤(Kyu Kon Kim); 김종원(Jong Won Kim); 엄현섭(Hyun Sup Eom); 지규용(Gyoo Yong Chi) (동의생리병리학회지, 2006)
In order to research the interrelationship of symptoms of 5 visceral diseases through Pearson's correlative coefficient and to understand the diagnostic importances of each symptom and sexual differences in the main symptoms of each visceral diseases using Cronbach alpha. For this 500 female and 120 male cases of questionnaire were collected and analyzed. In the main symptoms of 5 visceral diseases, there were a little differences between this results and existing symptom-complex system. And in the comparison of most frequently manifesting symptoms to male and female subject, Heart and Pancreas and Kidney disease were almost same, but Liver disease was different and Lung disease was slightly different. Conclusively, the diagnostic reliability of the abstracted symptom-complex of 5 viscera was graded from Kidney(Cronbach alpha 0.8771555), Pancreas(0.865978), Liver(0.815013), Heart(0.78653) to Lung disease(0.6294695) sequentially. And the each Cronbach alpha was valuable to be permitted as diagnostic criteria of 5 visceral diseases. KCI Citation Count: 4